Dialogic weaving: a favorable tension between design and craft. Issue 1 (2nd January 2019) - Altay, Can; Öz, Gizem
ABSTRACT: Focusing on a process where a designer embeds herself in craftspeople's workshops with the intention of 'learning from inside' and 'making together'; this paper proposes pathways for considering collaboration between designers and craftspeople via digital fabrication and weaving. The tension of forces that make weaving possible, act as an analogy for this collaboration as well as providing the title of the project as 'One Over, One Under'. The project proposes a mode of working and a spectrum of outcomes where the designer has a first-hand experience of production techniques, engages in a serious and continuous dialogue through making, and develops an intervention that also brings forth her own skill set (introducing digital fabrication and structural variations), thus transforming the conventions and boundaries between established roles and manufacturing techniques. An experiment that resulted in a series of objects considering both the technologies of production and the input of the designer, this process not only increases the potentials that crafts hold for the field of design, but it also offers possibilities of collaboration and a further articulation of the design act.